The comparison between the identity structure of the society and the physical structure of the city - Javadi, Farnaz; Noormohamadzad, Hossein (Journal of Architecture and Urbanism, 2017)
The concept of identity has the potential to be interpreted from the aspect of any field and according to requirements and abilities of that. Identity is defined as language, art, and thought of any phenomenon, and the relations between these components in an environment. These relations represent a range of similarities and dissimilarities. Structure is one of the concepts that can be tracked in different phenomena. Identity is a total, consisting of language, art, and thought that are related to each other by transformators, around regulators, in adherence to principles, which create the identity structure. Likewise, the physical structure of the city is the outcome of structure of its components that are related to each other by transformators, around regulators and in adherence to principles. This study aims to find out whether the identity structure of the society is in accordance with the physical structure of the city? The study has been performed by descriptive and comparative methods. Results show that the identity structure of the society is corresponded to the physical structure of the city in principles, components and constituents. As a result, the identity structure of the society is in accordance with the physical structure of the city.